Islam Politik: Kewajiban dan Tanggung Jawab Umat - Juwono, Hendro (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2018)
The awareness that encourages Muslims to return to the bosom of Muslims, among others, is to carry out politics, namely taking care of Muslim affairs by re-applying Islamic law in domestic and foreign affairs. Awareness born of his belief in Islam as the only complete religion and ideology. It is this awareness that gives birth to belief in Islam, that Islam is the only ideology that must be carried out by all humans so that their lives are kept away from the sadness that befalls and the beliefs that drive them to continue fighting for Islam so that Islam is applied. Therefore, this belief and awareness are the basis of political activity, so that political activity is a manifestation of mind and heart activity. Activities that cannot be killed by any force. But doing Islamization in various dimensions of life, especially regarding how the obligations and responsibilities of the people.